DeamiDATE 1.0: Site-specific deamidation as a tool to assess authenticity of members of ancient proteomes. (March 2020) - Ramsøe, Abigail; van Heekeren, Vivian; Ponce, Paola; Fischer, Roman; Barnes, Ian; Speller, Camilla; Collins, Matthew J.
Abstract: Contamination is a potential problem in the study of ancient proteins, either from prior handling of the sample, laboratory consumables, or cross-sample carryover from mass spectrometers. Recently, deamidation of glutamine has been proposed as a measure for assessing the degradation of ancient proteins. Here, we present deamiDATE 1.0, a method for the authentication of ancient proteins using measure of site-specific deamidation rates. We test this approach on shotgun proteomic data derived from bone collagen from modern, archaeological and extinct taxa. We further demonstrate how this method may be used to differentiate between modern contaminants and authentic ancient proteins using a case study from Neolithic dental calculus. Highlights: deamiDATE 1.0 discriminates between modern and ancient proteomes. Most current approaches to do this use bulk deamidation rates. deamiDATE 1.0 uses site-specific deamidation for more finely grained results. This allows detection of post-excavation contaminants.